T-helper cell receptors from long-term survivors after telomerase cancer vaccination for use in adoptive cell therapy. (1st December 2016) - Kyte, Jon Amund; Gaudernack, Gustav; Faane, Anne; Lislerud, Kari; Inderberg, Else Marit; Brunsvig, Paal; Aamdal, Steinar; Kvalheim, Gunnar; Wälchli, Sébastien; Pule, Martin
ABSTRACT: We herein report retargeting of T-helper (Th) cells against the universal cancer antigen telomerase for use in adoptive cell therapy. The redirected Th cells may counter tumor tolerance, transform the inflammatory milieu, and induce epitope spreading and cancer senescence. We have previously conducted a series of trials evaluating vaccination with telomerase peptides. From long-term survivors, we isolated >100 CD4 + Th-cell clones recognizing telomerase epitopes. The clones were characterized with regard to HLA restriction, functional avidity, fine specificity, proliferative capacity, cytokine profile, and recognition of naturally processed epitopes. DP4 is the most prevalent HLA molecule worldwide. Two DP4-restricted T-cell clones with different functional avidity, C13 and D71, were selected for molecular T-cell receptor (TCR) cloning. Both clones showed a high proliferative capacity, recognition of naturally processed telomerase epitopes, and a polyfunctional and Th1-weighted cytokine profile. TCR C13 and D71 were cloned into the retroviral vector MP71 together with the compact and GMP-applicable marker/suicide gene RQR8. Both TCRs were expressed well in recipient T cells after PBMC transduction. The transduced T cells co-expressed RQR8 and acquired the desired telomerase specificity, with a polyfunctional response including production of TNFa, IFNγ, and CD107a. Interestingly, the DP4-restricted TCRs were expressed and functional both in CD4 + and CD8 + T cells. The findings demonstrate that the cloned TCRs confer recipient T cells with the desired hTERT-specificity and functionality. We hypothesize that adoptive therapy with Th cells may offer a powerful novel approach for overcoming tumor tolerance and synergize with other forms of immunotherapy.